2017
DOI: 10.1155/2017/9340610
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Receptor Expressed on Myeloid Cells 2 Overexpression Inhibits Proinflammatory Cytokines in Lipopolysaccharide-Stimulated Microglia

Abstract: Microglia play an important role in mediating inflammatory processes in the central nervous system (CNS). Triggering receptor expressed on myeloid cells 2 (TREM2) is a microglia-specific receptor and could decrease neuropathology in Alzheimer's disease (AD). However, the detailed mechanism remains unclear. This study was designed to elucidate the effect of TREM2 on microglia. We showed that lipopolysaccharide (LPS) stimulation significantly increases proinflammatory cytokines and suppressed TREM2 in microglia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Previous findings showed that LPS stimulation suppressed TREM2 levels in microglia, at the same time inducing pro-inflammatory cytokines secretion (Zheng et al, 2016). Peripheral LPS challenge (at a similar dose to that used in our study) induced up-regulation of TREML2 and down-regulation of TREM2 levels in microglia, and increase of pro-inflammatory cytokines (Zheng et al, 2016; Zhang et al, 2017). In particular, reduction of TREM2 was associated with a decreased microglia proliferation, an effect that was absent when TREML2 was knocked down.…”
Section: Discussionmentioning
confidence: 61%
“…Previous findings showed that LPS stimulation suppressed TREM2 levels in microglia, at the same time inducing pro-inflammatory cytokines secretion (Zheng et al, 2016). Peripheral LPS challenge (at a similar dose to that used in our study) induced up-regulation of TREML2 and down-regulation of TREM2 levels in microglia, and increase of pro-inflammatory cytokines (Zheng et al, 2016; Zhang et al, 2017). In particular, reduction of TREM2 was associated with a decreased microglia proliferation, an effect that was absent when TREML2 was knocked down.…”
Section: Discussionmentioning
confidence: 61%
“…showing that TREM2 is a proinflammatory mediator and an inhibitor of phagocytic microglial activity. 38,39 Depletion of microglial TREM2…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, TREM2 is expressed in a specific macrophage subset in diseased aortas, which have been ascribed to lipid metabolism functions (20). Additionally, TREM2 dampens TLR signaling in several myeloid cell types (21,22), controls macrophage and microglia function (23,24) and directly binds apolipoprotein E and other atherogenic lipids (25)(26)(27). In fact, multiple members of the TREM family have been shown to exhibit lipid binding properties (28) which makes this family a remarkable target for modulating the intertwined relationship between lipid signaling and inflammation.…”
Section: Introductionmentioning
confidence: 99%